1986
DOI: 10.1130/spe208-p97
|View full text |Cite
|
Sign up to set email alerts
|

Processes of regional Tertiary extension in the western Cordillera: Insights from the metamorphic core complexes

Abstract: In the western United States, a major Tertiary extensional orogeny is distinguished from the more recent and subdued Basin and Range disturbance. This orogeny, characterized by dynamic horizontal translations (i.e., >100% extension in the Great Basin) occurred during the Eocene (-55-40 Ma) north of the Snake River Plain and during Oligocene-Miocene time (-35-16 Ma) farther south. Tectonic processes at shallow crustal levels included widespread listric or rotational faulting, decoupling along flat detachment fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

1988
1988
1998
1998

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 35 publications
0
26
0
1
Order By: Relevance
“…The tectonic regime is characterized by extensional mylonite zones, with younger-on-older faults in the allochton, in contrast to the mylonites and faults of the classic older-on-younger thrust and fold belts. Twenty-five such core complexes have been identified to date, discontinuously arrayed in a belt along the axis of the North American Cordillera, from northwest Mexico to British Columbia (DAVIS, 1980;DAVIS et al, 1980;REHRIG, 1986;REHRIG & REYNOLDS, 1980;REYNOLDS & REHRIG, 1980, for an overview see CONEY, 1980). Metamorphic core complexes are interesting from the standpoint of fluid regimes accompanying crustalscale deformation.…”
Section: Introduction and Scope Of Studymentioning
confidence: 97%
“…The tectonic regime is characterized by extensional mylonite zones, with younger-on-older faults in the allochton, in contrast to the mylonites and faults of the classic older-on-younger thrust and fold belts. Twenty-five such core complexes have been identified to date, discontinuously arrayed in a belt along the axis of the North American Cordillera, from northwest Mexico to British Columbia (DAVIS, 1980;DAVIS et al, 1980;REHRIG, 1986;REHRIG & REYNOLDS, 1980;REYNOLDS & REHRIG, 1980, for an overview see CONEY, 1980). Metamorphic core complexes are interesting from the standpoint of fluid regimes accompanying crustalscale deformation.…”
Section: Introduction and Scope Of Studymentioning
confidence: 97%
“…Estimates of uplift in the Snake Range of Nevada range from 6 or 7 km (Gans and Miller 1983;Miller et al 1983) to 15 km (Bartley and Wernike 1984) and are compatible with the amount of Eocene uplift suggested for the Valhalla complex (Parrish et al 1988) and suggested here for the Nelson batholith. In contrast with some of the metamorphic core complexes in the southwestern United States (Rehrig 1986), roof rocks of Canadian core complexes, such as the Valhalla and Okanagan complexes, appear to have been affected by significant uplift and thermal disturbance, probably as the result of their formation at deeper crustal levels. Core complexes of the southwestern United States are thought to have formed at shallow crustal levels as a result of high heat flow, shallow intrusion, and fluid-induced strain softening (Rehrig 1986).…”
Section: Discussionmentioning
confidence: 91%
“…The onset of the extensional deformation is emphasized rather than the age of continued faulting. In many areas of the Basin and Range province, extensional faulting may have begun in the Oligocene (Proffett, 1977;Crowe, 1978;Crowe et al, 1979;Rehrig, 1986;Snoke and Miller, 1988;Gans et al, 1989;). …”
Section: Southern Great Basinmentioning
confidence: 99%